Changes of gut microbiota in pregnant sows induced by 5-Aminolevulinic acid. (May 2021) - Chang, Mengru; Li, Mingcong; Li, Min; Xie, Yuhuai; Li, Yan; Yang, Weiren; Gao, Zheng
Abstract: Sow health is related to farm productivity and sustainability, but the increased resistance of bacteria to antibiotics in the pig industry has led to a decline in resistance to disease and environmental pollution. 5-Aminolevulinic acid (5-ALA) is considered a feed additive to replace antibiotics, but the effect of 5-ALA on gut microbiota has not been studied. In this study, we fed 12 healthy Landrace × Large White two-line hybrid sows with different concentrations of 5-ALA; blood and fecal samples were obtained after 110 days of pregnancy, and 16S rRNA amplicon sequencing was performed. The alpha diversity of the gut microbiota in sows was not significant among the sows fed different concentrations of 5-ALA. PCoA revealed a significant ( P  < 0.05) difference in the gut microbiota composition with different 5-ALA groups. LEfSe revealed that 5-ALA increased relative abundance of Streptococcus, while Myroides was enriched in CK group. Functional prediction of Tax4Fun showed that different concentrations of 5-ALA significantly ( P  < 0.05) increased the mean relative abundance of KEGG pathways involved in core microbiota cellular processes, environmental information processing, and genetic information processing. In summary, 5-ALA changed bacterial community composition of gut microbiota, reduced colonization of some pathogenes and increased the relative abundance of some probiotics. These results provide a theoretical basis for the healthy breeding of pigs. Highlights: The composition of gut microbiota in sows is changed by 5-ALA. 5-ALA increased the colonization of some gut probiotics (e.g. Streptococcus ). 5-ALA reduced the colonization of some gut opportunistic pathogens (e.g. Myroides ).